The impact of digitalization on the practice of determining economical cadastral valuation - Bykowa, Elena; Volkova, Jana; Pirogova, Oksana; Barykin, Sergey Evgenievich; Kazaryan, Ruben; Kuhtin, Peter (Frontiers in Energy Research, 2022)
Cadastral appraisers often use only those pricing factors that are mentioned in the National Standard of Cadastral Appraisal which leads to overestimation or underestimation of the cadastral value, therefore a shortage of budget funds and dissatisfaction among the citizens over the cadastral system of value for the taxation. This study aims to analyze the territory for the presence of local pricing factors, i.e. those that can be identified directly during zoning. Such factors can be, for example, soil quality, environmental health, proximity to waste storage, cell towers, etc. The work consists of the following steps: substantiating the composition of local cadastral value factors, collecting qualitative and quantitative values of cost factors ranking and normalizing the values of factors, checking market data for compliance with the normal distribution law, determining the type of functional dependence of prices on factors, building a model for calculating the cadastral value, analyzing the quality of a statistical calculation model. Approbation was carried out on the example of garden and garden plots located in the Belgorod region of the Russian Federation. The test results showed that the cadastral value model, which included local factors, is statistically significant and better describes the market.